Applying for jobs: Does ALMP participation help? - Rafael Lalive; Michael Morlok; Josef Zweimüller (University of Zurich, Department of Economics, 2011)
This paper calculates the impact of Active Labour Market Programmes through the use of three new indicators measuring the application performance of the unemployed. These indicators can be measured repeatedly and therefore allow the usage of Panel Regression methods, cancelling out any unobserved individual heterogeneity. To implement the new approach, data on 30,000 applications has been collected. Using this data, a large positive effect for unemployed with a long term unemployment forecast was estimated. For unemployed without such a forecast, the effect is much smaller. The paper also shows that the new evaluation approach fulfils the requirements of a good controlling instrument: It is accurate, detailed, non-intrusive, inexpensive and therefore easy to keep up to date, easy to understand and communicate.
Keywords: I38; J64; J68; 330; evaluation; treatment effect; active labour market program; job search; Arbeitsmarktpolitik; Beschäftigungseffekt; Schweiz